The Human Soul as a Manifestation of Quantum-Like Fields - Edward, W. Kamen; Roger, D. Kamen (Journal of Human Psychology, 2025)
It is proposed that the human soul is a manifestation of a soul field consisting of a collection of quantum-like fields. The soul field interacts with the electromagnetic field, manifested by photons interacting with the quanta of the soul field. Evidence for this comes from near-death experiences where reported events that could not have been seen through the eyes of the individual are verified. Since bioelectric fields are a type of electromagnetic field, bioelectric fields may also interact with the soul field. This could result in the transfer of information on working memory content to the soul via interactions with bioelectric fields produced by neural ensembles in the human brain. The soul field may also affect neurons on the molecular level in the brain through interactions with bioelectric fields and the recently proposed mechanism of cytoelectric coupling. The human soul is coupled to the body through its interactions with bioelectric fields in the body. Manifestations of the quantum-like fields comprising the soul field may carry out different functions such as encoding memories and experiences, representing emotion states, and defining personal identity. Interactions of these fields and their quanta could produce emergent properties such as self-awareness and consciousness.
Keywords: Human soul; soul field; near-death experiences; reincarnation; ephaptic coupling; cytoelectric coupling